2013
DOI: 10.1371/journal.pone.0057692
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Expression Is Associated with Acquisition of EMT Phenotype and with Enhanced Invasion in Erlotinib-Resistant Lung Cancer Cell Lines

Abstract: BackgroundThe epidermal growth-factor receptor tyrosine kinase inhibitors have been effective in non-small cell lung cancer patients. However, acquired resistance eventually develops in most patients despite an initial positive response. Emerging evidence suggests that there is a molecular connection between acquired resistance and the epithelial–mesenchymal transition (EMT). N-cadherin is involved in the EMT and in the metastasis of cancer cells. Here, we analyzed N-cadherin expression and function in erlotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 35 publications
(29 reference statements)
10
81
0
Order By: Relevance
“…ZNF750 overexpression resulted in decreased expression of the mesenchymal marker N-cadherin. N-cadherin expression is associated with the EMT phenotype and with enhanced invasion in cancer (20). N-cadherin serves an important role in the malignant behaviors of HNSCC (21).…”
Section: Discussionmentioning
confidence: 99%
“…ZNF750 overexpression resulted in decreased expression of the mesenchymal marker N-cadherin. N-cadherin expression is associated with the EMT phenotype and with enhanced invasion in cancer (20). N-cadherin serves an important role in the malignant behaviors of HNSCC (21).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, gradual increases of N-cadherin expression in these breast cancer cell lines were related to EMT-associated mechanisms, regardless of the E-cadherin expression [46], and could be used as stage markers during invasion processes. Furthermore, it has been reported that Ncadherin expression correlates with invasion and motility, plays a direct role in promoting motility, and is involved in EMT and cancer cell metastasis [47]. There are contradictory reports on the effects of estrogen on N-cadherin expression in different cell models; in most cancer cells, it has been shown to negatively regulate N-cadherin induced by the ER signaling pathway [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that Ncadherin expression correlates with invasion and motility, plays a direct role in promoting motility, and is involved in EMT and cancer cell metastasis [47]. There are contradictory reports on the effects of estrogen on N-cadherin expression in different cell models; in most cancer cells, it has been shown to negatively regulate N-cadherin induced by the ER signaling pathway [47]. We suggest that high N-cadherin levels initiate EMT but through a different method by which estradiol directly affects breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of E-cadherin is considered to be a fundamental event in EMT (27). N-cadherin and vimentin are mesenchymal cell markers, and they are closely related to cell invasion (28,29). In the present study, western blot analysis for E-cadherin, N-cadherin and vimentin protein expression was performed to investigate the effect of ARHI on EMT in colon cancer cells.…”
Section: Discussionmentioning
confidence: 96%